Simulating fatigue in squat jumps: A preliminary investigation - Bailey, C. A.; Sato, K. (Journal of Trainology, 2019)
Previous research has shown that fatigue is associated with decreases in performance and may result in joint instability that is associated with injury. Objectives: The purpose of this study was to determine if lightly loaded jumps could simulate fatigue from a lower body kine matic perspective. Design and Methods: Seventeen NCAA DI baseball players (height 1.8 m ± 0.7, body mass 87.5 kg ± 7.9) performed unloaded and lightly loaded (20 kg) squat jumps, while 3D motion capture data were collected via six infrared cameras and reflective markers. Kinematic data included range of motion (ROM), peak angular velocity (PV), position at PV (PPV), peak angular acceleration (PA), and position at PA (PPA) for both the hip and knee as well as jump height (JH). Comparisons between conditions were completed with paired samples t tests, along with Cohen`s d effect sizes and 95% confidence intervals. Results: Statistical differences were noted between condition`s PV at both joints (hip (p = 0.00, d = 0.63); knee (p = 0.000, d = 0.65) and for PA of the hip (p = 0.002, d = 0.55). A decrement in JH was also noted (p = 0.000, d = 1.13). Conclusions: The results of the current investigation indicate that a 20 kg load is enough to cause jump performance changes similar to those seen with previous research associated with fatigue. This may be particularly useful for coaches and sport scientists seeking to understand how athletes will perform while fatigued.